2018
DOI: 10.1111/jpn.13034
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Megasphaera elsdenii inoculation in subacute ruminal acidosis in cattle

Abstract: | INTRODUC TI ONNutritional management strategies in increase grain proportion to meet demand for energy should cover risk for and prevention of subclinical ruminal acidosis (SARA). It is characterized by increased total volatile fatty acid (VFA) concentration and propionate fraction and decreased ruminal pH (5.2-5.8) and acetate fraction. Meanwhile, ruminal lactate concentration exceeds 5-10 mM (Keunen et al., 2002).Ruminal pH kinetics parameters (i.e., minimal pH level and time below critical pH level) are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Furthermore, it has been reported that M. elsdenii utilizes lactate, glucose and maltose thus would compete with LAB for substrate, leading to reducing the lactate concentration and in the meantime enhancing VFA production [ 41 , 64 ]. It is also suggested that the efficacy of M. elsdenii on prevention of SARA might depend on the dietary grain types and the endogenous rumen microbiota, and meanwhile, the supplementation of this bacterial species can alter the rumen microflora by decreasing S. bovis counts and increasing protozoa counts [ 42 ]. However, the past research did not take the individualized rumen microbiome into account on how they respond to this DFM differently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been reported that M. elsdenii utilizes lactate, glucose and maltose thus would compete with LAB for substrate, leading to reducing the lactate concentration and in the meantime enhancing VFA production [ 41 , 64 ]. It is also suggested that the efficacy of M. elsdenii on prevention of SARA might depend on the dietary grain types and the endogenous rumen microbiota, and meanwhile, the supplementation of this bacterial species can alter the rumen microflora by decreasing S. bovis counts and increasing protozoa counts [ 42 ]. However, the past research did not take the individualized rumen microbiome into account on how they respond to this DFM differently.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, dairy ruminants are at high risks during these periods due to the stress from calving, changing diets from forage-based types to high-concentrate diets, and lactation as well as negative energy balance and potential inflammations or metabolic disorders. Some studies have reported that DFMs (mainly combination of LAB, LUB, or yeast) can improve milk production, feed efficiency and health performance in dairy cows [ 40 , 42 ], however, the efficacy was not consistent [ 122 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, when strains of Ruminococcus albus and Ruminococcus flavefaciens, all of which were isolated from the rumen, were inoculated into the rumen of adult sheep, the inoculants failed to persist or improve the intended fiber digestion [10]. Megasphaera elsdenii inoculation to the rumen of Holstein heifers suffering from subacute ruminal acidosis (SARA) did not increase the abundance of M. elsdenii or alleviate the SARA conditions although it altered the rumen VFA profiles [11][12][13]. Inoculation with whole rumen contents from non-milkfat-depressed cows only slightly accelerated the recovery of de novo synthesis of fatty acids in milk fatdepressed cows [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adverse effects including lowered feed intake and digestion often result at effective doses (Patra and Yu, 2014). Although from a microbiological perspective, rumen microbes of desired features can be inoculated into a rumen to improve certain aspects of the rumen function, such as fiber digestion, inoculation of the rumen of adult ruminants with Ruminococcus albus and R. flavefaciens did not enhance fiber digestion (Krause et al, 2001), while Megasphaera elsdenii inoculation did not attenuate subacute ruminal acidosis (SARA) (Klieve et al, 2003;Zebeli et al, 2012;Arik et al, 2019). Inoculation of dairy cows that exhibited milk fat depression with whole rumen content from non-milk fat-depressed cows only slightly accelerated the recovery of de novo synthesis of fatty acids (FA) in the former (Rico et al, 2014).…”
Section: Introductionmentioning
confidence: 99%